Cytological and microbiological profiling of body fluids: a study from Acharya Harihar Post Graduate Institute of Cancer, Cuttack, Odisha, India - Pradhan, Saumyasree; Dalai, Sushree Jasmin; Choudhury, Snigdharani; Das, Mahasweta (International Journal Of Community Medicine And Public Health, 2025)
Background: Body fluids play a crucial role in the human body, serving as the medium for biochemical reactions essential to cellular metabolism. They include intestinal fluids, saliva, tears, and gastric juice. The concentration of substrates in cellular fluids significantly influences the rate of metabolic reactions. Body fluids are typically found in the central nervous system (CNS), pericardial, pleural, peritoneal, and synovial spaces, comprising up to 60% water. Methods: The present study was conducted at Acharya Harihar Post Graduate Institute of Cancer (AHPGIC), Cuttack, over one month. A total of 25 fluid samples were collected from the Department of Pathology, AHPGIC. Pleural fluid was obtained through thoracocentesis, while peritoneal and ascitic fluids were collected via paracentesis. The fluids were drained using a syringe and aliquoted into tubes containing EDTA for cell counts and heparin for further studies. The collected samples were then transported in sterile containers and stored under refrigeration for further examination. For microbiological analysis, the collected fluids were inoculated in different culture media to facilitate the growth of microorganisms. Results: Among the 25 fluid samples analyzed, malignant cells were identified in pleural and ascitic fluids. However, Gram-positive and Gram-negative bacteria, as well as acid-fast bacteria, were not observed in any of the samples through direct staining. Conclusions: In culture, the growth of Gram-positive cocci was detected in peritoneal fluid, while Gram-negative bacilli were found in ascitic fluid.